Training and match volume and injury in adolescents playing multiple contact team sports: A prospective cohort study - Hartwig, T. B.; Gabbett, T. J.; Naughton, G.; Duncan, C.; Harries, S.; Perry, N. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Training and competition loads have emerged as valuable injury risk factors but very few studies have explored injury outcomes in adolescent athletes. The aims of this study were to describe injuries and to explore the relationship between training and match load volumes and injury in adolescent athletes participating in multiple contact team sports. One hundred and three male youth rugby athletes aged 14-16 years from 8 rugby union teams were prospectively monitored during a season for weekly training and match volumes and injuries. The relationship between volume and injury was explored by comparing the weekly volume in the week prior to an injury vs weeks without injury. There were 83 time-loss injuries in 58 athletes (62%). Overall injury incidence was 18.5 per 1000 player-hours. Mean weekly injury prevalence was 27% (95% CI 25-30). Average weekly volume was 5.4 (2.2) hours comprising 1.4 (1) match hours and 4 (2.6) training hours. Compared with weeks without injury, weeks prior to an injury had higher match volumes (110 [57] min vs 83 [59] min, P < 0.001). Poisson regression demonstrated that match volume was a predictor of injury with an odds ratio of 1.41 (P = 0.001). The contribution of match volumes to injury risk and the relatively high injury burden in these athletes may be profound. Very high match volumes are unlikely to be in the best interests of young athletes and could be avoided with a systematic approach to load management and athlete development.